Penerapan Metode Hanifida Tipe Gerak dan Lagu dalam Mengenalkan Al-Asma Al-Husna pada Anak Usia Dini - Ajeng Teni Nur Afriliani; Husna Waiyatuz Zahro (Institut Madani Nusantara, 2024)
Learning to introduce the 99 Asmaul Husna for early childhood actually provides its own difficulties for children, especially in recognizing and pronouncing them, this is because teachers lack variety in using learning methods. This study aims to introduce Al-Asma Al-Husna to early childhood using the Hanifida method. The Hanifida method is a fast and practical memorization method that is constructivist in nature, gradually building knowledge through visualization experiences, imagination, stories full of action and emotion created by the child themselves according to the real-life context. The classroom action research design was carried out collaboratively. This collaborative research was conducted by researchers and collaborated with teachers. The collaboration was a form of cooperation between researchers and class teachers of group B. This research was conducted in 2 cycles, the first cycle was carried out for 4 days and the second cycle was carried out for 5 days with the results after the actions in cycle I obtained results of 10% BB (not yet developed), 40% MB (starting to develop), and 50% BSH (developing as expected), then in cycle II the results obtained were 20% MB (starting to develop), and 80% (developing as expected). So the application of the Hanifida method of movement and song type in introducing Al-Asma Al-Husna and its meaning is very effective, this can be seen from the increase in children's development results in recognizing Al-Asma Al-Husna from each cycle both in quantity and quality.